The link between linguistic subordination and linguistic inferiority complexes: English as a second language migrants in Australia - Tankosic, Ana; Dryden, S.; Dovchin, Sender (SAGE PUBLICATIONS LTD, 2021)
Aims and objectives/purpose/research questions: This article aims to explore the link between linguistic subordination and linguistic inferiority complexes in the context of English as a second language (ESL) migrants in Australia. We address the following research questions: (a) To what extent and how do ESL migrants in Australia suffer from linguistic subordination? (b) To what extent and how is this linguistic subordination linked to linguistic inferiority complexes for ESL-migrants in Australia? (c) What are the main social implications of the link between linguistic subordination and linguistic inferiority complexes for ESL migrants? Design/methodology/approach: The study involved the participation of 150 participants who were observed using linguistic ethnography. The participants engaged in interviews and focus group discussions so that we could explore the psychological consequences of linguistic subordination that they encountered. Data and analysis: The interviews and focus group discussions were transcribed and analysed with consideration to the context, as well as the participants’ utterances and paralanguage. The study followed alternative quality criteria. Findings/conclusions: Many ESL migrants in Australia face linguistic subordination for the way they speak English. Consequently, these migrants suffer from linguistic inferiority complexes – psychological and emotional damages, which result in self-marginalisation, self-vindication, loss of sense of belonging, social withdrawal, fear, anxiety and the erosion of self-confidence. We find that there is a direct link between linguistic subordination and linguistic inferiority complexes. Originality: This article addresses a gap that exists regarding the link between linguistic subordination and the development of linguistic inferiority complexes, discusses how this has real-life consequences for ESL migrants, and explores how this may be overcome. Significance/implications: ESL migrants need support so that they can cope with their experiences of linguistic subordination, thus helping them better deal with issues related to linguistic inferiority complexes. In addition, the broader society needs greater education on how their comments and actions can affect the wellbeing of others.